Distribution of CD4+RORg-T Th17 and CD25+ FOXP3+ Treg in Leprosy Patient with Reversal Reaction - Renni Yuniati; Riawan W; Widasmara D; Darmaputra IGN; Arifin S (Faculty of Medicine, Diponegoro University, 2017)
Background: One of the most common difficulties found in leprosy management is how to manage leprosy reaction, even though MDT has proven to be effective for the patients. Reversal reaction is associated with cell mediated immunity (CMI), consists of T-helper (Th) 1 and Th2 activities. Moreover, subset of CD4+ Th17 and CD25+ FOXP3 Treg were known to have an important role in leprosy’s natural history. Prior study showed a decreasing number of CD25+ FOXP3 Treg and increasing number of CD4+ Th17 in type II reversal reaction (ENL). However, the distribution of Th17 and Treg in type I reversal reaction (RR) has not yet been identified.Objective: To compare the distribution of CD4+ Th17 and CD25+ FOXP3 Treg between RR and ENL patient groups.Method: A total of 50 samples, consisted of 27 samples of reversal reaction (RR) and 23 samples of ENL, were collected. Observation of CD4+ RORg-T Th17 and CD25+ FOXP3 Treg were conducted with immunohistochemistry staining technique using anti FOX-P3 and anti RORg-T. Expression of CD4+ ROR-g Th17 and CD25+ FOXP3 Treg in percentage were analyzed using T-test.Result: There is a significant difference in mean CD4+ ROR-g Th17 and IL17 cell distribution for RR patient group (14.96% and 10.72%) compared with ENL (9.12% and 4.28%). No significant difference were found between mean CD25+ FOXP3 Treg and TGF-β cell distribution in RR patient group (6.12% and 5.44%) compared with ENL group (6.16% and 5.96%).Conclusion: There is a significant increment od CD+RORg-T Th17 and IL17 in RR patients group compared with ENL patients group. however, the distribution of CD25+ FOXP3+ Treg and TGF beta in RR has no significant difference campared with ENL.